2016
DOI: 10.1148/radiol.2016152160
|View full text |Cite
|
Sign up to set email alerts
|

Optoacoustic Imaging of Human Vasculature: Feasibility by Using a Handheld Probe

Abstract: Purpose To investigate whether multispectral optoacoustic tomography (MSOT) developed for deep-tissue imaging in humans could enable the clinical assessment of major blood vessels and microvasculature. Materials and Methods The study was approved by the Institutional Review Board of the University Medical Center Groningen (CCMO-NL-43587) and registered in the Dutch National Trial Registry (NTR4125). The authors designed a real-time handheld optoacoustic scanner for human use, based on a concave 8-MHz transduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
111
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 124 publications
(116 citation statements)
references
References 31 publications
2
111
0
Order By: Relevance
“…The handheld optoacoustic imaging technology was also used in a feasibility study assessing peripheral blood supply and vascular disease in human feet. Such diagnosis is important in the context of peripheral arterial diseases, diabetic foot, and (autoimmune) vasculitis [331]. In this study, optoacoustic imaging has been shown to be superior to conventional imaging methods (e.g.…”
Section: Applications Enabled By Optoacoustic Visualization Of Multmentioning
confidence: 99%
“…The handheld optoacoustic imaging technology was also used in a feasibility study assessing peripheral blood supply and vascular disease in human feet. Such diagnosis is important in the context of peripheral arterial diseases, diabetic foot, and (autoimmune) vasculitis [331]. In this study, optoacoustic imaging has been shown to be superior to conventional imaging methods (e.g.…”
Section: Applications Enabled By Optoacoustic Visualization Of Multmentioning
confidence: 99%
“…PAI and US signals, for example, are detectable using the same equipment, making this pair attractive, as illustrated by a handheld hybrid US-MSOT probe for the visualisation of sentinel lymph nodes and the determination of their metastatic status in melanoma; in a 20-patient clinical trial 149 , indocyanine green (ICG) and melanin contrast were detected up to 5 cm in depth, and delivered 100% sensitivity and 48.6% specificity for metastatic status, as verified by histology. A similar US-MSOT system demonstrated simultaneous imaging of haemoglobin oxygen saturation and flow (Doppler US) in the vasculature of healthy human volunteers 150 , and frequency splitting in ultra-broadband optoacoustics identified inflammation parameters for the staging of psoriasis 151 . However, most state-of-the-art MSOT systems are still in prototypical design phase, which is a hurdle to regulatory approval and clinical adoption.…”
Section: Combining Data From Different Molecular Contrastsmentioning
confidence: 99%
“…MSOT has been shown to address a number of clinically relevant aspects such as tissue oxygenation or tumor spreading and can potentially overcome a number of other shortcomings in current surgical practice …”
Section: Introductionmentioning
confidence: 99%